2011
DOI: 10.1002/art.30157
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric systemic lupus erythematosus: Lessons learned from magnetic resonance imaging

Abstract: Objective. The clinical manifestations of nervous system involvement in systemic lupus erythematosus (neuropsychiatric SLE [NPSLE]) are highly diverse, and their etiology is incompletely understood. The aim of this study was to provide an inventory of abnormalities on conventional brain magnetic resonance imaging (MRI) in NPSLE and to interpret the findings in relation to possible underlying pathogenetic mechanisms.Methods. MR images of the first episode of active NPSLE in 74 patients were retrospectively revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
3
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 51 publications
4
132
3
9
Order By: Relevance
“…An underlying acute infarct has been suggested in areas where reduced diffusion was observed secondary to cytotoxic oedema, while bilateral WMHs are thought to be a sign of chronic hypoperfusion. 20 Common sites of WMH lesions are in the frontoparietal region, periventricular and subcortical white matter, and their presence has been recorded in both active and inactive NPSLE. 29,[47][48][49] Although evidence still persists that WMHs are not specific to NPSLE, as it was shown in SLE without overt neuropsychiatric involvement, they were found to be higher in quantity and total volume in active and past NPSLE when compared with non-NPSLE patient groups.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…An underlying acute infarct has been suggested in areas where reduced diffusion was observed secondary to cytotoxic oedema, while bilateral WMHs are thought to be a sign of chronic hypoperfusion. 20 Common sites of WMH lesions are in the frontoparietal region, periventricular and subcortical white matter, and their presence has been recorded in both active and inactive NPSLE. 29,[47][48][49] Although evidence still persists that WMHs are not specific to NPSLE, as it was shown in SLE without overt neuropsychiatric involvement, they were found to be higher in quantity and total volume in active and past NPSLE when compared with non-NPSLE patient groups.…”
Section: Discussionmentioning
confidence: 98%
“…Third, there is a chance that some of the NPSLE syndromes may (e.g. anxiety) develop later 19 Luyendijk et al 20 and Jennings et al 21 Fluid-attenuated inversion recovery (FLAIR)…”
Section: Study Eligibility and Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study in patients with newly diagnosed SLE, WMH were found in 8% of the patients 38 . Nevertheless, these lesions were observed more frequently in NPSLE when compared with SLE without neuropsychiatric manifestations, with average ranges from 40 to 60% 8, 11, 19, 34, 36, 38, 39 . WMH were associated with cerebrovascular disease, cognitive dysfunction, seizures, antiphospholipid antibodies, low complements (C3, C4, CH50), age, disease duration, and total corticosteroid dose 8, 34 .…”
Section: Introductionmentioning
confidence: 94%